Elevated angiopoietin-like protein 3 serum levels in diabetic nephropathy patients and its association with renal function and lipid profile - Samaneh Mohassel Azadi; Reza Fadaei; Ramtin Omid-Shafaat; Jalil Hosseini; Nariman Moradi (BMC Nephrology, 2023)
Abstract Background Type 2 diabetes mellitus (T2DM) is a highly prevalent disease that has life-threatening consequences like micro and macrovascular complication. Diabetic nephropathy (DN) is one of the common consequences of T2DM which is related to secretory factors like hepatokines. Angiopoietin-Like Protein 3 (ANGPTL3) is a hepatokine that is perturbated in cardiometabolic diseases and experimental studies showed its effect on renal functions and lipid metabolism. For the first time, ANGPTL3 was measured in patients with T2DM and DN in the present study. Methods Serum levels of ANGPTL3, IL-6, and TNF-α were measured in 60 healthy control, 60 T2DM patients, and 61 DN patients. Results Serum levels of ANGPTL3 increased in T2DM (252.39 ± 66.01) and DN (284.59 ± 69.27) patients compared to controls (160.22 ± 48.96), and DN patients compared with T2DM patients. Urinary albumin excretion (UAE) was higher in the DN group compared to T2DM and control groups. Moreover, serum levels of IL-6 and TNF-α were elevated in both patient groups compared to controls. Moreover, ANGPTL3 represented a positive correlation with triglycerides, creatinine, and UAE in patients with both T2DM and DN groups and showed an inverse correlation with eGFR in patients with DN. Moreover, this hepatokine had a good potential to differentiate patients from controls, especially, DN patients. Conclusions these findings provide invivo evidence for the relation of ANGPTL3 with renal dysfunction and hypertriglyceridemia in patients with DN which is in line with experimental findings and suggested a potential role for this hepatokine in DN pathogenesis.